Corporate Governance, Integrated Reporting and the Use of Credibility-enhancing Mechanisms on Integrated Reports. Issue 4 (7th August 2020) - Wang, Ruizhe; Zhou, Shan; Wang, Timothy
Abstract : The International Integrated Reporting Council (IIRC) and the South African King III Report on Governance emphasize the role of corporate governance in preparing a high-quality integrated report and establishing an appropriate credibility-enhancing process. This paper examines the significance of corporate governance mechanisms in explaining variations in the quality of integrated reports and the extent and quality of credibility-enhancing mechanisms (CEMs) for integrated reports. Using a sample of integrated reports published between 2012 and 2015 by listed companies on the Johannesburg Stock Exchange, this study finds that traditional governance mechanisms such as the board and the audit committee are positively related to the reporting quality of and use of CEMs. In addition, sustainability-oriented corporate governance mechanisms (i.e. sustainability committee and the use of non-financial performance measures in executives' compensation contracts) have an incremental positive effect on both the quality of and the extent and quality of CEMs on integrated reports. Additional analyses attribute the positive effect of these corporate governance mechanisms on quality and the use of CEMs mainly to the diligence and expertise of the board of directors and audit committee and the independence and expertise of a sustainability committee.